The Commonwealth — a name for the State or Also Its Guiding Idea? An Outline of the Issue - Łabno, Anna (A thousand years of Poland’s presence among the elite of European states, 2026)
Republican thought was of fundamental importance to Polish constitutionalism. In the fifteenth century, the term "Rzeczpospolita" was used for the first time — a term that not only became part of the name of the state, but also identified it as the common good. This concept refers to the idea of a community of citizens united under a single law and forming a single state. The Rzeczpospolita is the highest political value and the common good. The Constitution of 1921 uses the term "Rzeczpospolita" to describe the form of the state. Meanwhile, the Constitution of May 3rd, the April Constitution, and the Constitution of 1997 all continue the traditions inaugurated in the fifteenth century. The term "Rzeczpospolita" signifies that the Polish state is the common good of all its citizens.